Influence of the Exchange-Correlation Functional on the Energy of Formation and Magnetic Behavior of Binary D03 Intermetallic Compounds FeM3 (M = Ti, Zr, Hf) - Gil Rebaza, Arles Víctor (2017)
In recent years, ab-initio calculations based on the density functional theory became a commonly used tool in supporting, improving or even refuting experimental results in different research fields. In this work we discuss some accuracy aspects inherent to ab-initio electronic structure calculations regarding the understanding of different structural, electronic and magnetic physical properties. In particular, we discuss the dependence of the magnetic ground-state and the formation energy with the exchange-correlation functional for the binary intermetallic compounds FeTi3, FeZr3 and FeHf3 with D03 crystal structure. All exchange-correlation schemes used were based on the generalized gradient approximation. It is the aim of the present paper to call the attention of the community to some fundamental aspects of the calculations that can influence the final results and the conclusions derives from it.